The Work of the Holy Spirit in the Conception, Baptism and Temptation of Christ: Implications for the Pentecostal Christian Part I - Phanon, Yuri (Asian journal of pentecostal studies, 2017)
The article discusses the three stages of the life of Christ and shows how each stage is associated with the Holy Spirit. Topics covered include the work of the Holy Spirit in the conception and baptism of Christ, an examination of the stages of Jesus' life by exegeting on several significant passages in the Gospels, and the implications of the Holy Spirit's work for Pentecostal Christians.